Planar Cardinal Spline Curves with Minimum Strain Energy (Communications in Mathematical Research, 2019)
In this paper, we focus on how to use strain energy minimization to obtainthe optimal value of the free parameter of the planar Cardinal spline curves. Theunique solution can be easily obtained by minimizing an appropriate approximationof the strain energy. An example is presented to illustrate the effectiveness of ourmethod.
Keywords: Cardinal spline; Catmull-Rom spline; minimization; strain energy; fair curve